Pola Kemitraan Pengembangan Wisata Perkebunan Kopi di Desa Ketapanrame Mojokerto - Dia Ayu Nur Alifah; Indah Rachma Nur Halimah; Amanda Qolbi Shafira; Deasy Rizki Masruroh; Chantika Maria Margareta Putri; Agil Putri Fatmasari; Dana Rejasa; Muchtarrom Visandy (Mitra Teras: Jurnal Terapan Pengabdian Masyarakat, 2025)
This study aims to describe, identify, and analyze partnership patterns in the development of coffee plantation tourism in Ketapanrame Village, Trawas District, Mojokerto Regency. The focus of this study is on partnership patterns involving the village government, farmer groups, village-owned enterprises (BUMDes), academics, and private sector entities, based on three forms of partnership as outlined pseudo-partnership, mutualistic partnership, and conjugal partnership. This study employs a qualitative descriptive method with data collection techniques including field observation, interviews, and documentation. Research informants were selected through purposive sampling, including the Village Head of Ketapanrame, the Head of the Tourism Management Unit, and representatives of the coffee farmer group. This study finds that the development of coffee plantation tourism in Ketapanrame Village has progressed well through multi-stakeholder collaboration. The village government plays a key role in providing capital, institutional legalization, land utilization, and facilitating partnerships with external actors. Mutualistic and conjugative partnership models positively contribute to farmers’ capacity building, institutional strengthening, and the promotion of coffee educational tourism, while pseudo-partnerships should be minimized through open communication and clear agreements. The study highlights the importance of targeted strategies to ensure partnership sustainability and optimize coffee tourism as a driver of the local economy.    Abstrak Penelitian ini bertujuan untuk mendeskripsikan, mengetahui dan menganalisis pola kemitraan dalam pengembangan wisata perkebunan kopi di Desa Ketapanrame, Kecamatan Trawas, Kabupaten Mojokerto. Fokus penelitian ini adalah pola kemitraan yang melibatkan pemerintah desa, kelompok tani, BUMDes, akademisi serta pihak swasta dengan mengacu pada tiga bentuk kemitraan yaitu kemitraan semu, kemitraan mutualistik dan kemitraan konjugasi. Penelitian ini menggunakan metode deskripsitf kualitatif dengan teknik pengumpulan data melalui observasi lapangan, wawancara dan dokumentasi. Informan penelitian ditentukan secara purposive sampling yang meliputi Kepala Desa Ketapanrame, Ketua Unit Pengelolaan Wisata dan perwakilan kelompok tani kopi. Penelitian ini menunjukkan bahwa pengembangan wisata perkebunan kopi di Desa Ketapanrame berjalan baik melalui kolaborasi multipihak. Pemerintah desa berperan dalam penyediaan modal, legalisasi kelembagaan, pemanfaatan lahan, serta fasilitasi kerja sama dengan mitra eksternal. Pola kemitraan mutualistik dan konjugasi berdampak positif terhadap peningkatan kapasitas petani, penguatan kelembagaan, dan pengembangan wisata edukasi kopi, sementara potensi kemitraan semu perlu diminimalkan melalui komunikasi terbuka dan perjanjian yang jelas. Penelitian ini menegaskan pentingnya strategi terarah untuk menjaga keberlanjutan kemitraan dan mengoptimalkan wisata kopi sebagai penggerak ekonomi lokal.